2020
DOI: 10.1287/mnsc.2019.3461
|View full text |Cite
|
Sign up to set email alerts
|

Wage Transparency and Social Comparison in Sales Force Compensation

Abstract: When wages are transparent, sales agents may compare their pay with that of their peers and experience positive or negative feelings if those peers are paid (respectively) less or more. We investigate the implications of such social comparisons on sales agents’ effort decisions and their incentives to help or collaborate with each other. We then characterize the firm’s optimal sales force compensation scheme and the conditions under which wage transparency benefits the firm. Our results show that the work envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Li et al (2020) constructed a behavioral model, including "byexpectation fairness" and "by-state fairness," and motivated their experimental observations to explain managers' effort and order decisions under different compensation contracts. Long and Nasiry (2020) investigated the implications of social comparison on agents' effort decisions as well as the firm's optimal compensation scheme. However, our work is Production and Operations Management different from theirs in the following manner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2020) constructed a behavioral model, including "byexpectation fairness" and "by-state fairness," and motivated their experimental observations to explain managers' effort and order decisions under different compensation contracts. Long and Nasiry (2020) investigated the implications of social comparison on agents' effort decisions as well as the firm's optimal compensation scheme. However, our work is Production and Operations Management different from theirs in the following manner.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2020) compared linear and non-linear contracts and showed that the feature of fairness plays a role in the realized outcomes, leading to a reduction in the benefits of non-linear contracts. Additionally, Long and Nasiry (2020) discussed the advisability of making wages transparent to employees. The incentive-design issue becomes more complicated with multitasking agents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We do not care how people obtain the peers’ information for comparisons interpersonally. Recently, [ 37 ] identified the conditions; thereby a company should reveal wage information to its employees, resulting in social comparisons. They found that social comparisons reduce collaborations interpersonally but could increase their willingness to ally for lowering the cost of effort.…”
Section: Happiness For Willingness-to-workmentioning
confidence: 99%